Unexpected Pregnancy and Ovarian Hyperstimulation Syndrome Following Ivf Cycle with all Embryos Frozen: A Case Report - Chi-Feng Fu; Tsung-Hsien Lee; Chin-Der Chen; Mei-Jou Chen; Hong-Nerng Ho; Yu-Shih Yang (Elsevier, 2005)
Objective: We report a patient with late onset of severe ovarian hyperstimulation syndrome (OHSS) combined with pregnancy subsequent to in vitro fertilization (IVF) cycles without embryo transfer, which is extremely rare. Case Report: This case of severe OHSS was in a 27-year-old woman who underwent controlled ovarian hyperstimulation (COH), oocyte collection, and IVF. All embryos were cryopreserved to prevent possible OHSS due to an extremely high level of estradiol (6,357 pg/mL). No embryo was transferred in this cycle. However, she was admitted 7 days after oocyte retrieval because of massive ascites and enlarged ovaries. Pregnancy was diagnosed by serum β-human chorionic gonadotropin (51 mIU/mL) 4 days later. Fetal heartbeat was demonstrated by ultrasound examination during follow-up. Conclusion: Prompt recognition of pregnancy and proper medical intervention should be given to patients with late-onset OHSS, even if no embryo was transferred in the fresh cycle. We suggest that more preventive procedures for OHSS may be necessary for patients undergoing COH and receiving no embryo transfer, such as oocyte donors and patients with polycystic ovary syndrome.